THE DENSITY FUNCTIONAL THEORY STUDY OF Li-ION DIFFUSION IN Na-DOPED Li4Ti5O12 AS LITHIUM-ION BATTERY ANODE - Achda Fitriah; Anugrah Azhar; Adam Badra Cahaya; Edi Suprayoga; Muhammad Aziz Majidi (Program Studi Fisika Universitas Negeri Jakarta, 2022)
Spinel phase lithium titanate (Li4Ti5O12 or LTO) has been studied as an alternative anode material with a “zero-strain” characteristic structure to improve safety, cycling stability, and rate performance. LTO offers stable Li-ion diffusion at a higher charge-discharge rate without noticeable structural change. However, LTO exhibits low electronic conductivity and low Li-ion diffusion compared to graphite-based anode materials, limiting its rate capability. In this study, we investigate the impact of Na atom doping on the diffusion rate in the Li4Ti5O12 (LTO) spinel phase using the density functional theory (DFT). Based on the nudged elastic band (NEB) calculation, we obtain the energy barrier values and each diffusion pathway, with barrier energy varying about 0.3 0.4 eV and affecting the value of the diffusion constant obtained. The study reveals the role of Na atom doping in the lithium-ion diffusion in NaxLi4-xTi5O12 for battery anode material.